EFEITOS DO LORAZEPAM E DO DIAZEPAM SOBRE O FLUXO PLASMATICO EFETIVO RENAL - Vianna, P. T.G.; Kiy, Y.; Cerqueira Braz, J. R. (My University, 1979)
The authors studied the effects of lorazepam and diazepan in 16 patients, when used in preanesthetic medication, on the effective renal plasmatic flow. In eight patients, diazepan was the only drug used and in the other eight only lorazepam. It is concluded that both the drugs do not produce significant fall of FPER.
Effects of lorazepam and diazepam on effective renal plasma flow